Characterization of archaeal community in Luzhou‐flavour pit mud. Issue 4 (16th September 2015) - Wu, Chongde; Ding, Xiaofei; Huang, Jun; Zhou, Rongqing
<x xml:space="preserve">Abstract</x> The aim of this study was to investigate the archaeal community in different ages of pit mud by a combined fluorescence in situ hybridization (FISH) and polymerase chain reaction–denaturing gradient gel electrophoresis (PCR‐DGGE) method. Four probes were used to detect the major methanogenic archaea by FISH experiments, and the results showed that orders Methanosarcinales, Methanobacteriales, Methanomicrobiales and Methanococcales were detected in the various ages (50, 100 and 300 year) of pit mud, except for the 1 year‐old pit and the 100 year‐old sample, which exhibited the highest numbers of archaea. The amounts of the four methanogenic archaea significantly increased from the 50 to 100 year‐old pit mud and slightly decreased in the 300 year‐old pit mud. Results of PCR‐DGGE analysis suggest that all archaeal 16S rRNA gene sequences fall into the phylum Euryarchaeota, and Methanobacteriales and Methanomicrobiales dominated in low‐age (1 and 50 year) and old age (100 and 300 year) of pit mud, respectively. Analysis of the community diversity based on the DGGE profiles showed that the 100 and 300 year samples exhibited similar diversity indices compared with the 1 and 50 year samples. This is the first report about the archaeal community structure in different ages of pit mud determined by both FISH and PCR‐DGGE analysis. Copyright © 2015 The Institute of Brewing & Distilling